Serum Level of 25-Hydroxyvitamin D in Children with Epilepsy Receiving Long-Term Antiepileptic Treatment - Ismail, Chasan; Irawan, Roedi; Saharso, Darto (MEDICINUS, 2020)
Background: Long-term treatment with antiepileptic drugs (AED) requires monitoring of potential side effects, one of them is the decreasing in serum vitamin D level. Low serum vitamin D level is also a global health problem in healthy children. There are conflicting results regarding the low serum vitamin D level in epileptic children due to treatment with AED. Purpose: This study aimed to compare serum vitamin D level between healthy children and children with epilepsy receiving long-term AED treatment in Soetomo General Hospital. Methods: This was a cross-sectional study conducted in the pediatric neurology clinic of Soetomo general academic hospital from August 2018 to July 2019. Subjects are children ages 2-18 years with epilepsy receiving AED treatment for over 6 months (n=22), with healthy children as control (n=22). Peripheral serum 25-hydroxyvitamin D level were measured using enzyme-linked fluorescence assay (ELFA) method. The differences of those groups were analyzed by comparing the mean of 25-hydroxyvitamin D level of both groups using Anova and T-test (95% CI). Results: Low serum vitamin D level were identified in 27% children with epilepsy and 13% healthy children. The mean of serum 25-hydroxyvitamin D level in children with epilepsy and healthy children was 21.5 ng/ml (SD 8.41) and 34.3 ng/ml (SD 10.09), respectively. There was a significant difference between groups (p<0.05). Conclusion: Children with epilepsy receiving long-term AED treatment have lower level of serum 25-hydroxyvitamin D than healthy children.